Perdagangan Bebas ASEAN dan Implikasinya terhadap Pertumbuhan Ekspor Indonesia ke ASEAN - Rambe, Aqli Nadzhari; Imsar, Imsar (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the impact of the ASEAN Free Trade Area (AFTA) policy on Indonesia’s export growth to ASEAN markets, with a specific focus on the agricultural sector as a key driver of the national economy. The main problem addressed is that, despite the elimination of tariffs under AFTA, Indonesian exporters still face significant non-tariff barriers, including stringent product quality standards, complex customs procedures, and regulatory disparities among ASEAN member states. The purpose of this research is to provide a comprehensive evaluation of both the quantitative benefits and the persistent technical and structural challenges of AFTA implementation. Using a literature review approach, the study analyzes secondary data from 2015 to 2024 obtained from credible sources, including government institutions, ASEAN reports, and international trade organizations. The results reveal that AFTA has significantly increased Indonesia’s export value in various subsectors such as palm oil, fisheries, horticulture, and processed food products. The removal of trade tariffs has enhanced market access, improved competitiveness, and encouraged investment in the agricultural sector. However, the study also finds that non-tariff barriers remain a major obstacle to maximizing AFTA’s benefits. As its novelty, this research not only assesses the quantitative growth of exports but also examines in depth the nature of non-tariff barriers and evaluates government policy responses, such as the harmonization of standards and the implementation of the National Single Window system. The study recommends strengthening inter-agency coordination and regional cooperation to fully optimize the benefits of ASEAN free trade.